Intraperitoneal Magnesium Sulphate-Bupivacaine Vs Tramadol-Bupivacaine for Pain Relief Post Laparoscopic Cholecystectomy: A Comparative Cross-Sectional Study - Mishra, Rohit Kumar; Raya, Akash; Shrestha, Alok; Yadav, Basant Kumar (Journal of College of Medical Sciences-Nepal, 2025)
Background Intraperitoneal analgesics in combination with local anesthetics are being widely used which leads to less rescue analgesic demand. This study aims to compare the effect of Magnesium Sulphate-Bupivacaine with Tramadol-Bupivacaine. Methods An analytical cross sectional study was conducted in the Department of Surgery of Chitwan Medical College from July 2024 to November 2024. Ethical approval was taken from Institutional review committee of CMC-TH (Ref No. CMC-IRC/080/081-145). The study included 82 cases in total, all of whom were admitted for laparoscopic cholecystectomy. Magnesium Sulphate-Bupivacaine patients were recruited into group MB, while Tramadol-Bupivacaine patients were recruited into group TB using lottery technique. Group MB was given 30 ml of 0.25% bupivacaine together with 30 mg/kg of magnesium sulphate, while Group TB was given 30 ml of 0.25% bupivacaine along with 100 mg tramadol and magnesium plus bupivacaine. The Visual Analogue Scale was used to measure post-operative pain, the demand and consumption for rescue analgesia. Results After 1, 2, 3, and 6 hours following surgery, the TB group’s cumulative mean VAS pain score was higher than the MB group’s (p = 0.0001), according to six VAS scores collected over a 24-hour period. The MB group consumed less rescue analgesia overall over the course of the 24-hour period (p=0.0001), and their mean time interval for the first rescue analgesia (paracetamol) demand was higher than that of the TB group. Conclusions In contrast to intraperitoneal administration of tramadol and bupivacaine during laparoscopic surgery, intraperitoneal administration of MgSO4 and bupivacaine showed a longer duration of pain-free period and a lower post-operative intake of rescue analgesics.